Vertical dynamic response of an end-bearing pile considering the nonlocal effect of saturated soil. (May 2020) - Wang, Ning; Le, Yi; Tong, Lihong; Fang, Tao; Zhu, Bitang; Hu, Wentao
Abstract: Although the classical Biot theory has been widely used in geotechnics, the simplifying assumption that the wavelength is much larger than the pore size may not conform to practical circumstances. Therefore, the nonlocal Biot theory, in which the effects of pore size and porosity dynamics are lumped into a nonlocal parameter, was proposed by others. In this paper, the nonlocal Biot theory is extended to investigate the vertical dynamic response of an end-bearing pile in saturated soil. The analytical solution for the vertical vibration of the pile in the frequency domain is obtained using Helmholtz decomposition and Laplace transform. The corresponding semi-analytical solution in the time domain for the pile under a semi-sinusoidal excitation is derived by inverse Fourier transform. The convergence and accuracy of the present solution is examined by degrading the nonlocal Biot theory into the classical Biot theory. The validation of the present solution is verified by comparing the results of the local theory with the nonlocal theory with a small nonlocal parameter. A parametric study is implemented to investigate the influence of the nonlocal parameter on the vertical dynamic response of a pile and the interplay between the soil properties and nonlocal effects.